Emanações: discursos fotográficos e culturais - Marangoni, Fábio Nutti (2015)
This dissertation is presented along with the authorial artistic product of Emanations. The work presents a unique artistic expression combining the photographic and literary languages, exposing viewers from a cosmopolitan standpoint. It reveals the artistic and sociological potential of a single photographic referent (workers in the cassava production in the Brazilian Amazonas state), offering society innovative communicative alternatives. The methodology contemplates fieldwork involving photographic production and a bibliographic review articulated around selected authors: Aristotle, Umberto Eco and Boaventura Souza Santos. The dissertation establishes multi-layered viewpoints that dialog with Emanations through the following disciplines: social sciences, cultural and visual anthropology supported by historical and memorial aspects, semiotics of the photographic image, late-modern aesthetic philosophy, contemporaneous photographic techniques and languages, as well as deductive processes. These elements compose a set of articulated discourses that favor photographic aesthetics as an open work in harmony with a post modernity that offers multiple possibilities for cultural and artistic development. The combination of the dissertation and the artistic work generates debate about new forms of production and the adept creation of a conceptual visual literature, aware of the multiple realities and artistic scenarios of the contemporary world. The artistic product represented by the photo-book contains black-and-white photographs that dialog with poetic prose converted into ekphrasis, the Aristolean metaphysics substance. The artwork reveals photos with striking social concern, adding dignity to the considerable labor done by the cassava workers. It enables a multicultural discussion around emerging themes that are still marginalized by hegemonic western rationality. The artisanal activity of the cassava flour producers is manifested through photographic language and autonomous literary language, breaking away from academic pictorialism and approaching the contemporaneous experimental aesthetics of new photography. Keywords: ekphrasis, neorealist aesthetic, photo-romance, new photography, poetic prose.